ONCOPLASTIC MAMMOPLASTY WITH GEOMETRIC COMPENSATION TECHNIQUE IN AN OLDER ADULT PATIENT - Alem, Christine Elisabete Rubio; Pires, Douglas Miranda; Paulinelli, Regis Resende (Mastology, 2018)
Breast cancer is a neoplasm of high incidence in women, which has been increasingly affecting older adult patients. Conservative breast surgery has changed the history of Mastology. Oncoplastic techniques and breast reconstruction are used in pursuit of better harmony between oncological treatment and cosmetic results. This study reports the case of an older adult patient submitted to oncological mammoplasty with geometric compensation technique.